The Relationship Between Mother's Pregnancy History and Baby's Birth to the incidence of stunting in infants - Anjar Astuti; Yanik Muyassaroh; Murti Ani (Journal of Midwifery Science: Basic and Applied Research, 2020)
One of the nutritional problems faced by children under five in the world, especially in developing countries is stunting. The problem of stunting in infants can have an impact on intellectual decline, increase the risk of non-communicable diseases, giving birth to babies with low birth weight and the risk of degenerative diseases in the future. So it is necessary to take preventative measures in order to reduce the stunting prevalence rate that is increasing every year. The purpose of this study: to determine the relationship between maternal pregnancy history and the history of the baby's birth to the incidence of stunting in infants. Research methods: using a retrospective cohort design with a sample of 85 mothers who have stunting toddlers. Results: Analysis of data using the chi square test of birth length (p = 0,000 0.05) has a relationship with the incidence of stunting while anemia during pregnancy (p = 0.212 0.05), chronic energy shortages during pregnancy (p = 0.837 0.05) and low birth weight (p = 0.297 0.05) had no relationship with the incidence of stunting. Conclusion: there was no significant relationship between maternal pregnancy history (Anemia and KEK), history of birth of the baby (LBW) and nutritional care patterns (accuracy of breastfeeding MP) with the incidence of stunting in infants. There is a significant relationship between the history of the birth of a baby (length of body birth) can cause stunting in infants. Suggestion: the results of this study can be taken into consideration to conduct early intervention appropriately to reduce the stunting rate in Blora Regency. Keywords: History of maternal pregnancy, history of baby's birth, toddler stunting.